1988
DOI: 10.2118/15651-pa
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of a Crude-Oil-Sulfonate/Nonionic-Cosurfactant Micellar Fluid

Abstract: Phase behavior, interfacial tension (1FT) measurements, fractionation studies, and core tests have been used in the formulation of a crude-oil-sulfonate (CROS)/ethoxylated-alcohol micellar fluid for application in a changing ionic environment that attains a relatively high hardness concentration as a result of ion exchange. By varying the hydrophile/lipophile balance (HLB) of the nonionic cosurfactant, phase behavior can be shifted from lower to upper phase and the optimum can be found. It is shown that the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The formulation is conducted by mixing amphoteric SAE with nonionic (ester group) surfactants. This differentiates with previous authors who mixed anionic with nonionic surfactants (Kremesec et al 1988;Martiz et al 2015) or anionic with cationic surfactants (Li et al 2016).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The formulation is conducted by mixing amphoteric SAE with nonionic (ester group) surfactants. This differentiates with previous authors who mixed anionic with nonionic surfactants (Kremesec et al 1988;Martiz et al 2015) or anionic with cationic surfactants (Li et al 2016).…”
Section: Introductionsupporting
confidence: 73%
“…Nonetheless, study by Martiz used pure alkane and the interfacial tension was above 10 mN/m, while most enhanced oil recovery purposes require interfacial tension of oil-water below 10 − 2 mN/m. Kremesec et al (1988) studied mixtures of anionic crude oil sulfonate and nonionic ethoxylated alcohol surfactants and they observed through laboratory experiments that low IFT and good solubilization parameter could be achieved by optimizing the HLB of nonionic surfactant. Marhaendrajana et al (2017) showed that sulfonated alkyl ester (SAE) surfactant reduces the interfacial tensions of both heavy and light oil samples with water in a wide range of salinity with monovalent and divalent ions present.…”
Section: Introductionmentioning
confidence: 99%